PENGARUH MANAJEMEN WAKTU, BUDAYA KERJA, DAN ETIKA KERJA PERSONEL ACO TERHADAP KESELAMATAN PENERBANGAN DI PERUM LPPNPI CABANG SURABAYA - Dewi Ratna Sari; Didi Hariyanto; Fatmawati Fatmawati; Laila Rochmawati (Politeknik Penerbangan Surabaya, 2020)
To become an international standard aviation navigation service provider, Perum LPPNPI Surabaya carries a mission to provide flight navigation services that prioritize safety, flight efficiency, and are environmentally friendly. The purpose of this study was to determine the effect of time management, work culture, and work ethics of ACO personnel on aviation safety at Perum LPPNPI Surabaya. This study uses multiple linear regression techniques to analyze the magnitude of the relationship and the influence of the independent variables. From the research that has been done, it is found that the value of the coefficient of determination or R square is 0.949 which means that the variables of time management (X1), work culture (X2), and work ethics (X3) simultaneously (together) have a strong effect on aviation safety variable (Y) is 94.9%. From the results of the T-test, it is found that the t-count value of the time management variable is 2.182> t table of 2.09302, the t value of the work culture variable is 2.676> t table of 2.09302, the t value of the work ethic variable is 2.686> t table of 2.09302 which as a whole, it can be interpreted as having an effect on aviation safety variables at Perum LPPNPI Surabaya.